(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Each year, there are an estimated 6 million new cases of syphilis globally in persons aged 15 to 49 years. Syphilis remains a risk factor among Men Sex with Men and other groups who tend to have multiple sex partners. As is known, people who suffer from syphilis increase the risk for contracting and transmitting HIV infection to others. This is because the mode of transmission of Syphilis and HIV have in common. Syphilis among Men Sex with Men needs special attention because if it is not immediately addressed it is likely to enter the heterosexual population and the impact will be even greater. Method: A cross sectional study: Integrated Behavior Biological Survey (IBBS) in 2015 is managed by the Ministry of Health every four years as part of evaluating HIV AIDS programs in Indonesia. The study was conducted in 6 selected provinces to 1,496 Men Sex with Men, behavioral data collection was done by interview while biological data in this case Syphilis and HIV were carried out by laboratory examination of blood samples Results: Studies show that syphilis is a risk factor for HIV with (95% CI) RR = 2.2 (1.8 - 2.8). The combination of syphilis, education level and condom use consistently increases the risk to 2.5 (1.03 - 5.84). Conclusions: There is a association between syphilis positive and HIV positive. Syphilis increases the risk of HIV cases up to 2 times among Men Sex with Men. Syphilis continues to be an uncontrolled public health problem with high rates of syphilis re-infection among Men Sex with Menpopulation in Indonesia. Prevention as a more effective approach can be done simultaneously considering that both Syphilis and HIV can be prevented in the same way